2021
DOI: 10.3390/toxins13090625
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Zearalenone on Selected Hemostatic Parameters in Sexually Immature Gilts

Abstract: Vascular toxicity induced by xenobiotics is associated with dysfunctions or damage to endothelial cells, changes in vascular permeability or dysregulation of the vascular redox state. The aim of this study was to determine whether per os administration of zearalenone (ZEN) influences selected hemostatic parameters in prepubertal gilts. This study was performed on female gilts divided into a control group which received placebo and an experimental group which received ZEN at a dose of 5.0 µg·kg−1 b.w. × day−1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…In turn, ERβ silencing increases the risk of duodenal inflammation and enhances oncogenesis not only in the gastrointestinal tract, but also in the reproductive system [ 22 , 40 , 45 , 46 , 57 ]. Deletion processes suggest that ERβ has anti-inflammatory and anti-carcinogenic properties, and exerts chemopreventive effects in the colon [ 58 ], which was confirmed in a study of low-dose ZEN mycotoxicosis [ 59 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In turn, ERβ silencing increases the risk of duodenal inflammation and enhances oncogenesis not only in the gastrointestinal tract, but also in the reproductive system [ 22 , 40 , 45 , 46 , 57 ]. Deletion processes suggest that ERβ has anti-inflammatory and anti-carcinogenic properties, and exerts chemopreventive effects in the colon [ 58 ], which was confirmed in a study of low-dose ZEN mycotoxicosis [ 59 ].…”
Section: Discussionmentioning
confidence: 93%
“…Apart from the previously published research on the effects of E 2 deficiency in prepubertal animals, another issue should be addressed. Williams et al [ 46 ] and Gajęcka et al [ 59 ] reported that selected phytoestrogens (silymarin and silibinin) and mycoestrogens (ZEN) have a selective affinity for ERβ [ 60 , 61 ]. This is the result of the increased expression of the ERβ gene, suggesting that natural exogenous dietary oestrogens may have anti-inflammatory properties [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value reported herein was lower than that of Jakimiuk et al . [ 45 ] for both controls and stress-challenged gilts. Previous studies have shown that CAT activity increases in response to oxidant concentration [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%